Unpackaging E-governance within the Perceptive of Community Development: A review of Selected Services in Uganda - Ayoma, Godfred; Ajok, Semmy; Amito, Catherine; Obele, Phedru; Okullu, Daniel; David Mwesigwa, David Mwesigwa (International Journal of Public Policy and Administration, 2024)
Purpose: This study aimed to review the relationship between e-governance and local community development by specifically, focusing on four selected services, viz., universal education, youth welfare, reproductive health and agricultural development in Uganda. Methodology: The study took a review of obtainable secondary literature by specifically looking at online materials both published works such as journal articles, policy statements, statistical reports as well as annual and/or quarterly reports. The choice of secondary literature, organized thematically, provided a wider purview of the scattered, yet vital aspects, pertaining e-governance in social service delivery. Findings: The outcomes, from the review, indicate that Uganda has made several in-roads regarding universal primary education, youth welfare programs, reproductive healthcare services and agricultural development through various interventions aided by e-governance platforms. However, a number of systemic and structural challenges continue to pull-back national and local efforts especially seen from online mechanisms. Unique contribution to theory, practice and policy: This review contributes immensely to the modern community transformation mooted in a digital era where enabling policies and practices can benefit from by reversing the impingements as well as the consolidating the success stories. We encourage the need for government to prioritize lowering the cost of internet services as a way of enhancing local community development; government should make sure that schools offering universal education should be facilitated with functional computer laboratories; government hospitals, at district level, should have a computer laboratory for data storage; and handy apps for farmers should be given priority so as to enhance smart agricultural development.